Are the Generic Scales Enough to Measure Service Quality of Mobile Banking? A Comparative Analysis of Generic Service Quality Measurement Scales to Mobile Banking Context. Issue 3 (3rd July 2019) - Shankar, Amit; Datta, Biplab; Jebarajakirthy, Charles
Abstract: The purpose of this study is to examine the service quality in the mobile banking (m-banking) context using different generic service quality scales, and to see which one is most appropriate to examine service quality in this context. Data were collected through structured questionnaires from 323 m-banking users in India. Unidimensionality, reliability, validity, and variance explained were the major criteria of comparison for generic service quality measures. The findings indicate that no measurement scale is suitable to measure m-banking service quality. This study provides the managers of financial institutions with some clear insights into consumers' service quality expectations of m-banking.